2015
DOI: 10.1128/ec.00076-15
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Chemical Diversity in Echinocandin Lipopeptide Antifungal Metabolites

Abstract: The echinocandins are a class of antifungal drugs that includes caspofungin, micafungin, and anidulafungin. Gene clusters encoding most of the structural complexity of the echinocandins provided a framework for hypotheses about the evolutionary history and chemical logic of echinocandin biosynthesis. Gene orthologs among echinocandin-producing fungi were identified. Pathway genes, including the nonribosomal peptide synthetases (NRPSs), were analyzed phylogenetically to address the hypothesis that these pathway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
63
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(64 citation statements)
references
References 88 publications
(133 reference statements)
1
63
0
Order By: Relevance
“…With this background, the example of pneumocandin biosynthesis in G. lozoyensis (Helotiales), which is by far the best-documented system among the echinocandin producers [2,7,9,[17][18][19][20] is now examined in an effort to ascertain if one of the models can be applied to echinocandin biosynthesis. During pneumocandin fermentation development at Merck & Co. Research Laboratories, over two dozen different pneumocandins were identified [9], with the chemical structures being reported for 16 of these derivatives.…”
Section: Comparison Of Pneumocandin Biosynthesis With Models For the mentioning
confidence: 99%
See 1 more Smart Citation
“…With this background, the example of pneumocandin biosynthesis in G. lozoyensis (Helotiales), which is by far the best-documented system among the echinocandin producers [2,7,9,[17][18][19][20] is now examined in an effort to ascertain if one of the models can be applied to echinocandin biosynthesis. During pneumocandin fermentation development at Merck & Co. Research Laboratories, over two dozen different pneumocandins were identified [9], with the chemical structures being reported for 16 of these derivatives.…”
Section: Comparison Of Pneumocandin Biosynthesis With Models For the mentioning
confidence: 99%
“…The history of exploring echinocandin biosynthesis has been featured in previous review articles [1,2,[7][8][9]. In brief, the biosynthetic origin of the non-proteinogenic amino acids and the dimethylmyristate side chain was elucidated in the early 1990s by groups of Tang and Walsh disclosed the genes encoding echinocandin B biosynthesis in the genome of Aspergillus pachycristatus NRRL 11440 (formerly Emericella rugulosa) [13].…”
Section: Introductionmentioning
confidence: 99%
“…echinulatus ) (Nyfeler & Keller-Schierlein 1974), A. parvathecius, A. navahoensis , A. quadrilineatus , A. rugulosus and A. pachycristatus (= “ Aspergillus nidulans var. roseus ” nomen nudum ) (Boeckner and Kastner, 1981, Klich et al., 2001, de la Cruz et al., 2012, Matsuzawa et al., 2012, Bills et al., 2014, Yue et al., 2015). Aflatoxin production is observed in A. astellatus ( = E. astellata ), A. venezuelensis (= E. venezuelensis ) and A. olivicola (= E. olivicola ) (Frisvad and Samson, 2004, Frisvad et al., 2004, Zalar et al., 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Gene organizations point to aculeacin 74 as having the most ancient biosynthesis pathway, whereas FR190293 81 has the most evolved one. Since no sign of horizontal gene transfer from bacteria could be observed, an origin of echinocandin biosynthesis in the genus Aspergillus can be assumed [120,121].…”
Section: From Papulacandins and Echinocandins To Drugs Against Fungalmentioning
confidence: 99%